Is it all in the hinge? A kryptoracemate and three of its alternative racemic polymorphs of an aminonitrile. Issue 6 (26th November 2015) - Laubenstein, R.; Şerb, M.-D.; Englert, U.; Raabe, G.; Braun, T.; Braun, B.
Abstract : A kryptoracemate, a racemic crystal in a Sohncke space group, and three additional polymorphs, well-ordered racemic structures. Abstract : Four polymorphs of 2-(perfluorophenyl)-2-(phenylamino)acetonitrile have been crystallized and structurally analyzed: in addition to three racemic crystals, a rare kryptoracemate has been obtained. The central single bonds allow for conformational flexibility: the kryptoracemate as well as two of the remaining polymorphs contain several independent molecules with different conformation. In contrast to these uncommon packing modes, the fourth phase is unexceptional and crystallizes with a single molecule in the asymmetric unit. Individual crystallization batches may contain several crystal forms concomitantly.